The Political Glass Cliff: Understanding How Seat Selection Contributes to the Underperformance of Ethnic Minority Candidates. (March 2014) - Kulich, Clara; Ryan, Michelle K.; Haslam, S. Alexander
An archival study of U.K. General Election results from 2001, 2005, and 2010 revealed that Conservative black and minority ethnic (BME) candidates were less successful than their white counterparts. However, mediation analyses demonstrate that this lack of success can be explained by the lower winnability of BME candidates' seats, such that the opposition candidate held a seat with a significantly larger majority compared with white candidates' opponents. Results and implications are discussed in the framework of the "glass cliff, " previously demonstrated for women, in the sense that the seats minority groups contested were harder to win compared with majority groups.